O Espaço ocupado pelo Homem Pré-Histórico no Oeste Paulista: O caso do Sítio Arqueológico Lagoa São Paulo - 02 no Município de Presidente Epitácio - SP - Cabrera, Jean Ítalo de Araújo [UNESP] (2015)
The hypothesis considered in this work is to prove that the Archaeological Site Lagoa São Paulo - 02 has been an area of population attraction where different people occupied this space for millennia because of abundance of raw material for manufactured goods, as well as the great diversity of flora and fauna in the region where the site is located. This work also aims to assess the contribution that an archaeological survey can provide in understanding the formation of geographical space and their transformations. Either for geography as in archeology the study of the techniques is fundamental, since it is through them that man can measure their cultural level. To try to understand these techniques are the key piece to know what the habits and customs of prehistoric peoples were, because through these techniques we discover what their way of life was and its relation to the occupied space. Thus we can see that in a more comprehensive analysis through knowing their techniques, we may be describing the customs of the peoples who inhabited a region...